10.1152/physiolgenomics.00169.2022 (CrossRef Listing of Deleted DOIs, 2000)
The incidence of type 1 diabetes mellitus (T1DM) has increased worldwide over recent decades. Early disease recognition reduces the occurrence of complications. This study aimed to determine if a community health education intervention utilizing a storytelling teaching method could increase knowledge and awareness regarding T1DM among underserved communities to promote early recognition. Six pharmacy students delivered educational sessions at various venues using standardized materials, including pamphlets, poster boards, and a narrative case titled "Recognizing the Signs: Bella's Story." The story illustrated the progression of unrecognized T1DM leading to complications, and discussions about common symptoms, risk factors, and management. Pre- and postsurveys assessed knowledge and perceived awareness and confidence. A paired t test was used to determine statistical differences. A total of 124 individuals attended the sessions, with 100 completing both surveys. Mean knowledge scores were 54.41% ± 24.19 vs. 87.47% ± 16.32, pre- vs. postsurvey, respectively, with improvements observed across all knowledge-based questions. Participants demonstrated substantial gains in self-reported awareness of symptoms and confidence in recognizing warning signs. Approximately 90% of participants indicated that the storytelling method was effective, and 87% reported learning new information. These findings suggest that storytelling-based community education is an effective strategy to enhance knowledge and awareness of T1DM and may support earlier recognition and prevention of severe complications in underserved populations.NEW & NOTEWORTHY This study addresses a critical gap in type 1 diabetes mellitus (T1DM) education by focusing on early symptom recognition rather than disease management after diagnosis. Using a storytelling-based community intervention, we demonstrated significant improvements in knowledge, awareness, and confidence among adults in underserved populations. Notably, no prior studies have evaluated storytelling to promote earlier identification of T1DM. These findings highlight an innovative, scalable approach to reduce delayed diagnosis and prevent life-threatening complications such as diabetic ketoacidosis.